A comparison of classification approaches for threat detection in CT based baggage screening - Megherbi, Najla; Han, Jiwan; Breckon, Toby P.; Flitton, Greg T. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Computed Tomography (CT) based baggage security screening systems are of increasing use in transportation security. The ability to automatically identify potential threat item is a key aspect of current research in this area. Here we present a comparison of varying classification approaches for the automated detection of threat objects in cluttered 3D CT imagery from such security screening systems. By combining 3D medical image segmentation techniques with 3D shape classification and retrieval methods we compare five varying final classification stage approaches and present significant performance achievements in the automated detection of specified exemplar items.
Keywords: aviation security; 3D medical image segmentation; 3D Zernike descriptors; histogram of shape index; automated classification; 3D object recognition